Magnetization and magnetic phases of conduction-band dilute-magnetic- semiconductor quantum wells with non-step-like density of states - Simserides, C. (International Journal of Modern Physics B, 2004)
We study the magnetization and the magnetic phases of II-VI-based n-doped non-magnetic-semiconductor (NMS) / narrow to wide dilute-magnetic-semiconductor (DMS) / n-doped NMS quantum wells under in-plane magnetic field. The parallel magnetic field is used as a tool, in order to achieve non-step-like density of states in these -appropriate for conduction-band spintronics- structures.